코탄젠트
http://bomber0.myid.net/ (토론)님의 2009년 7월 11일 (토) 14:15 판
코탄젠트의 테일러급수
\(\cot x = \frac {1} {x} - \frac {x}{3} - \frac {x^3} {45} - \frac {2 x^5} {945} - \cdots = \sum_{n=0}^\infty \frac{(-1)^n 2^{2n} B_{2n} x^{2n-1}}{(2n)!}\)
코탄젠트의 부분분수 전개
\(\pi \cot \pi\tau=\frac{1}{\tau}+\sum_{m\neq0}\frac{1}{\tau+m}-\frac{1}{m}\)
코탄젠트의 푸리에급수
\(\pi \cot \pi\tau=\pi\frac{\cos \pi\tau}{\sin\pi\tau}=\pi i \frac{e^{i\pi\tau}+e^{-i\pi\tau}}{e^{i\pi\tau}-e^{-i\pi\tau}}=\pi i \frac{e^{2\pi i \tai}+1}{e^{2\pi i \tai}-1}\)
\(\pi i \frac{q+1}{q-1}=\pi i (\frac{q}{q-1}+\frac{1}{q-1})=-\pi i (\sum_{r=1}^{\infty}q^r+\sum_{r=0}^{\infty}q^r)=-\pi i (1+2\sum_{r=1}^{\infty}q^r)\)
위의 두 표현에서 다음을 얻는다
\(\frac{1}{\tau}+\sum_{m\neq0}\frac{1}{\tau+m}-\frac{1}{m} = -\pi i (1+2\sum_{r=1}^{\infty}e^{2\pi i r \tau})\)